The Influence of Good Corporate Governance, Firm Size, and Profitability on Firm Value in Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Oksarini, Amalia; Hariyanto, Dedi; Safitri, Heni (UNIVERSITAS PAKUAN, 2025)
This research aims to investigate the effect of Good Corporate Governance (GCG), firm size, and profitability on firm value among property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The study employs a quantitative approach with an associative method. A sample of 74 companies was selected through purposive sampling based on predetermined criteria. Secondary data were collected using documentation techniques and analyzed using multiple linear regression with SPSS software. The results demonstrate that, simultaneously, independent commissioners, institutional ownership, audit committee, firm size, and profitability significantly affect firm value, with an adjusted R² of 87.4%. Partially, the variables of independent commissioners, institutional ownership, firm size, and profitability have a significant effect on firm value, while the audit committee does not. These findings highlight the critical role of strong corporate governance practices, optimal firm scale, and profitability in enhancing firm value. The study provides practical implications for corporate strategy and future research in the field of corporate performance measurement.